Human spleen microanatomy: why mice do not suffice. Issue 3 (July 2015) - Steiniger, Birte S.
Summary The microanatomical structure of the spleen has been primarily described in mice and rats. This leads to terminological problems with respect to humans and their species‐specific splenic microstructure. In mice, rats and humans the spleen consists of the white pulp embedded in the red pulp. In the white pulp, T and B lymphocytes form accumulations, the periarteriolar lymphatic sheaths and the follicles, located around intermediate‐sized arterial vessels, the central arteries. The red pulp is a reticular connective tissue containing all types of blood cells. The spleen of mice and rats exhibits an additional well‐delineated B‐cell compartment, the marginal zone, between white and red pulp. This area is, however, absent in human spleen. Human splenic secondary follicles comprise three zones: a germinal centre, a mantle zone and a superficial zone. In humans, arterioles and sheathed capillaries in the red pulp are surrounded by lymphocytes, especially by B cells. Human sheathed capillaries are related to the splenic ellipsoids of most other vertebrates. Such vessels are lacking in rats or mice, which form an evolutionary exception. Capillary sheaths are composed of endothelial cells, pericytes, special stromal sheath cells, macrophages and B lymphocytes. Human spleens most probably host a totally open circulation system, as connections from capillaries to sinuses were not found in the red pulp. Three stromal cell types of different phenotype and location occur in the human white pulp. Splenic white and red pulp structure is reviewed in rats, mice and humans to encourage further investigations on lymphocyte recirculation through the spleen.